2008
DOI: 10.1378/chest.08-1311
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Eye Movement-Related Sleep-Disordered Breathing

Abstract: REM SDB prevalence decreases with age in women as does REM AHI/NREM AHI, perhaps secondary to a disproportionate age-dependent rise in NREM vs REM AHI in women. Younger women may be protected from SDB during NREM sleep, even in the face of obesity. These patterns may reflect age-related decreases in female hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
113
6
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 14 publications
19
113
6
5
Order By: Relevance
“…1,2,16 However, in the current study, we adopted the aforementioned formula to avoid division by zero, which is in case AHI-NREM is zero. REM-predominant OSA defined by AHI-REM/AHI-NREM > 2 would be equal to %AHI in NREM ≤ 33.3% in our formula.…”
Section: The Definition Of Nrem-or Rem-predominant Osamentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,16 However, in the current study, we adopted the aforementioned formula to avoid division by zero, which is in case AHI-NREM is zero. REM-predominant OSA defined by AHI-REM/AHI-NREM > 2 would be equal to %AHI in NREM ≤ 33.3% in our formula.…”
Section: The Definition Of Nrem-or Rem-predominant Osamentioning
confidence: 99%
“…1,2 In general, upper airway obstruction and hypopnea is in REM sleep when upper airway muscle tonus is decreased as compared to nonrapid eye movement (NREM) sleep. However, OSA occurring predominantly in NREM sleep or equally in a numeric manner in both REM and NREM sleep is also encountered in clinical practice; neither prevalence nor mechanisms driving the relative distribution of REM and NREM events have been considered in any detail.…”
mentioning
confidence: 99%
“…Üst hava yolu tonusu non-REM uykuda azalır ve REM uykuda da azalmaya devam eder, böylece üst hava yolu rezistansında ve kollapsında artış meydana gelir. Ayrıca, uykunun REM evresinde hipoksi ve hiperkapniye meduller duyarlılık azalır ve tüm bunların sonucunda REM'de daha fazla solunumsal olayların yanında daha fazla oksijen desatürasyonu olur (2)(3)(4)(5).…”
Section: Introductionunclassified
“…In studies that used diagnostic criteria similar to ours, AHI have ranged between 10% and 13% (16,17 Because of differences in the definition criteria, in cases with REM-related OSAS, clinical characteristics also demonstrate differences. In many studies, a higher incidence of REM-related OSAS has been reported in women (3,6,12,13,19,20). Higher AHI REM relative to AHI NREM in women suggest the protection of women from respiratory events in NREM sleep.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of REM-related OSAS varies within a wide spectrum (10-36%) (6,(11)(12)(13). These highly variable outcomes stem from differences in criteria used for the definition of REM-related OSAS.…”
Section: Discussionmentioning
confidence: 99%